Predominant expression of circulating CD3+ lymphocytes bearing gamma T cell receptor in a prolonged immunodeficiency after allogeneic bone marrow transplantation. - Vilmer, E (1988)
The cell surface expression of alpha:beta heterodimer was studied using WT31 monoclonal antibody, in peripheral blood lymphocytes (PBL) from a patient who developed a prolonged immunodeficiency after allogeneic bone marrow transplantation. This patient, grafted for chronic myelogenous leukemia, received T cell depleted bone marrow from her HLA, A, B, D matched sibling. The late occurrence of opportunistic infection, led us to analyze the phenotype of patient PBL. 70% of PBL were CD3+ and 29% WT31+, indicating that the majority of CD3+ PBL did not express the alpha:beta heterodimer. Transcription of the genes encoding the alpha, beta, and gamma chains was assessed in cell lines derived from PBL, by Northern blot analysis. We showed that the CD3+ WT31- subset expressed a truncated, beta mRNA (1.0 kb) and also truncated alpha transcript (1.4 kb). To determine the CD3-associated structure on CD3+ WT31- cell line, immunoprecipitation assays were performed using monoclonal anti-CD3 and an hetero antiserum against gamma peptides. These CD3+ WT31- cells expressed a disulfide linked dimer, composed of products of gamma gene (37 kD, 40 kD) and of undefined delta chain (45 kD). Functional analyses were performed in PBL before and after sorting with WT31 and anti-CD3 antibody. These circulating CD3+ WT31- cells were unable to proliferate when triggered with anti-T3 beads and they seemed to mediate a suppressor activity on CD3+ WT31+ cells.